Disordered eating risk and well-being in women with lipedema - Kunzová, Monika (Frontiers in Global Women's Health, 2026)
BackgroundLipedema is a chronic adipose tissue disorder predominantly affecting women and is frequently misclassified as obesity. While its physical manifestations are increasingly recognized, less attention has been paid to eating attitudes and psychological well-being in this population. The objective of this study was to descriptively explore eating attitudes and psychological well-being in women with lipedema.MethodsThis exploratory cross-sectional study used an anonymous online survey to describe eating attitudes and psychological well-being in women with lipedema. A total of 47 participants completed the Eating Attitudes Test (EAT-26) and the World Health Organization-5 Well-Being Index (WHO-5). Descriptive statistics were used to summarize screening indicators of disordered eating risk and reduced psychological well-being.ResultsApproximately two-thirds of participants scored at or above the EAT-26 screening cut-off, reflecting elevated screening indicators of disordered eating risk. When behavioral risk indicators were included, over 70% screened positive according to EAT-26 criteria. Reduced psychological well-being (as indicated by a WHO-5 score of ≤50) was observed in about one-fifth of the sample.ConclusionIn this exploratory sample of women with lipedema, elevated screening indicators of disordered eating risk and reduced psychological well-being were commonly observed. These findings offer preliminary insights suggesting that eating-related risk and reduced well-being may be prevalent in this population. Further research using larger, clinically verified samples is needed to better understand the psychological aspects of lipedema.